Helicopter nonlinear aerodynamics modelling using VehicleSim. (October 2016) - Castillo-Rivera, S.; Tomas-Rodriguez, M.
Highlights: The aerodynamic loads on a helicopter model are implemented with VehicleSim. All the dynamics, aerodynamic forces and control action are embedded in a single code. The nonlinear equations of the system are provided by VehicleSim. This new tool may be used to develop robust control methods. Abstract: This work describes a model developed to analyze the aerodynamic loads on a helicopter model on conventional configuration implemented with VehicleSim, a multibody software specialized in modelling mechanical systems composed by rigid bodies. The rotors are articulated and the main rotor implementation takes into account flap, lag and feather degrees of freedom for each of the equispaced blades as well as their dynamic couplings. This article presents an aerodynamic model that allows to simulate hover, climb, descent and forward flight as well as trajectories under the action of several aerodynamics loads. The aerodynamic model has been built up using blade element theory. All the dynamics, aerodynamic forces and control action are embedded in a single code, being this an advantage as the compilation time is greatly reduced. The software used in this work, VehicleSim does not need external connection to other software. This new tool may be used to develop robust control methods. The nonlinear equations of the system which can be very complex, are obtained, in particular, this article presents the equations for flap and lag degrees of freedom in hover flight. The control approach used in here consists of PID controllers (proportional, integral, derivative), which allow to use VehicleSim command exclusively to simulate several helicopter flight conditions. The results obtained are shown to agree with the expected behaviour.